Sawit Off Grade Sebagai Bahan Baku Alternatif Pembuatan Biodiesel Melalui Proses Dua Tahap Menggunakan Katalis Zeolit Alam Yang Dimodifikasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm off grade is a sort of CPO mill utilization wich is not maximized. Palm off grade produced approximately 7-10% of the processing capacity of the plant CPO. Oil-palm off grade has a high free fatty acid contents, so it needs two stage process to produce biodiesel. The purpose of this research is to produce biodiesel with a maximum yield above 90%, determine the effectiveness of biodiesel production using a two-stage process with natural zeolite catalysts and determine the effect of temperature, mole ratio of oil : methanol and the concentration of catalyst to biodiesel yield. In this research, natural zeolite modified using 75% KOH solution. Then, biodiesel production have done in two stage, that was esterification and transesterification with variation of temperature (50°C, 60°C,70°C), mole ratio of oil : methanol (1: 6, 1: 8, 1:10) and concentration of catalyst (2%-w, 4%-w, 6%-w) in transesterification. The result of this research was processed with Response Surface Methodology (RSM) and the number of stepswas determined by Central Composite Design (CCD). The highest yield of biodiesel is 96.99% at temperature 60°C, mole ratio of oil : methanol 1: 8 and concentration catalyst 4%-w. The result showed that the process conditions which influencing the yield of biodiesel is the reaction temperature and catalystconcentration.Keywords: biodiesel, natural zeolite, off grade palm oil, response surface methodology.